Evaluation of Lignocellulolytic Fungal Consortium for Composting Sugarcane Bagasse, Filter Cake and Manure - Rahmad, R; Nurmiaty, N (KnE Life Sciences, 2022)
Three lignocellulolytic fungi isolates, Amblyosporium sp, Aspergillus sp1, and Aspergillus sp2, were tested for their ability to produce cellulase, hemicellulose, and ligninase enzymes as a consortium. They were also used in a mixture with sugarcane bagasse, filter cake and manure to make mixed compost. In the compost house of the State Agricultural Polytechnic of Pangkep, composting took place for 35 days. The composting process of the consortium of lignocellulolytic fungi was carried out at a temperature of 32°C-75°C, , with a water content of 12.58-30.32% and a pH of 6.80-8.20. The 35-day lignocellulolytic fungal consortium was able to speed up the composting process with a C-organic yield of 10.41-26.06%, a C/N ratio of 9.00-22.00%, phosphorus of 1.98%, magnesium of 6866 ppm, and sulfur of 0.25%. The fungal consortium was able to effectively speed up the composting process while also increasing nutrient content in various composting media compositions. Keywords: Fungi, lignocellulolytic, sugarcane, bagasse, manure